FORMATION OF INTERCITY AIR ROUTES IN KARAKALPAKSTAN - Kitaybekov Azizbek (Web of Journals Publishing, 2024)
This article talks about the formation of air transport in Karakalpakstan and the history of the formation of transport routes between districts and cities.
Keywords: Karakalpakstan, aircraft, airways, Tortkul, plane, link.